2020
DOI: 10.1007/978-3-030-20249-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Values, Beliefs and Environmental Citizenship

Abstract: In this chapter, we will consider the relationships between values, beliefs and Environmental Citizenship. The role of personal values, value orientations and environmental beliefs in explaining pro-environmental actions and behaviour is widely explored. It is already acknowledged that self-enhancement (egoistic and hedonistic) values are less predictive of pro-environmental actions than self-transcendence (biospheric and altruistic) values. Additionally, beliefs are considered to be at the core of human behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This signifies that an individual's values, such as altruistic values, are not an appropriate predictor of pro-environmental behaviour as altruism is more people-oriented than environment-oriented. As noted by Balunde et al [ 118 ], biospheric values (an altruistic values subset) are more closely related to environmentally favourable outcomes. Hence, it can be concluded that our sample consists of people who might have different values that are responsible for a negative relationship between altruistic motivation and pro-environmental belief.…”
Section: Discussionmentioning
confidence: 96%
“…This signifies that an individual's values, such as altruistic values, are not an appropriate predictor of pro-environmental behaviour as altruism is more people-oriented than environment-oriented. As noted by Balunde et al [ 118 ], biospheric values (an altruistic values subset) are more closely related to environmentally favourable outcomes. Hence, it can be concluded that our sample consists of people who might have different values that are responsible for a negative relationship between altruistic motivation and pro-environmental belief.…”
Section: Discussionmentioning
confidence: 96%
“…However, this also raises the need to look into participants' willingness to change their beliefs when confronted with evidence that contradicts their current point of view. It may be that various individual characteristics such as values or personality traits would moderate the effectiveness of learning about environmental issues (Balundė et al 2020;Jia et al 2017;Poškus, 2020;Poškus and Žukauskienė, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still teachers who are new to the term, and there are teachers who state that they do not know and do not understand. Previous study identify three broad views concerning contemporary environmental issues: anthropocentrism, ecocentrism, and technocentrism (Balundė et al, 2020). This complete view can be used to identify values that are relevant to pro-environmental behavior and environmental citizenship.…”
Section: Discussionmentioning
confidence: 99%